Swimming Upstream: Struggling Firms in Corrupt Cities - Parsons, Christopher A.; Sulaeman, Johan; Titman, Sheridan (Journal of Financial and Quantitative Analysis, 2025)
Abstract We find that a corrupt local environment amplifies the effects of financial distress. Following regional spikes in financial misconduct, credit becomes more difficult to obtain for local borrowers—even those not implicated themselves. This is particularly harmful for cash-constrained firms, which cut investment more sharply and lay off more workers during industry downturns. We also find that local clustering of financial misconduct is a risk factor for bankruptcy.